2008
DOI: 10.1097/sla.0b013e31817f2bfd
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Hilar Cholangiocarcinoma

Abstract: In patients with hilar cholangiocarcinoma, concomitant hepatic resection is associated with improved DFS, DSS, and decreased hepatic recurrence. Therefore, hepatectomy combined with bile duct resection should be considered standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(65 citation statements)
references
References 28 publications
2
62
0
1
Order By: Relevance
“…32 Bile duct resection combined with major hepatectomy is increasingly recognized as the standard treatment for HC, improving the obtainment of R0 resections and long-term survival. 3,4,12 In our study, the rate of R0 resections was higher with associated liver resection than with biliary confluence resection alone (79.2% vs 65.6%; P=.01). Of course, this type of resection is challenged by the close relationship between tumor and vascular structures at the hepatic hilum.…”
Section: Commentmentioning
confidence: 49%
“…32 Bile duct resection combined with major hepatectomy is increasingly recognized as the standard treatment for HC, improving the obtainment of R0 resections and long-term survival. 3,4,12 In our study, the rate of R0 resections was higher with associated liver resection than with biliary confluence resection alone (79.2% vs 65.6%; P=.01). Of course, this type of resection is challenged by the close relationship between tumor and vascular structures at the hepatic hilum.…”
Section: Commentmentioning
confidence: 49%
“…However, controversy still surrounds the choice of the procedure for patients with Bismuth type I and II cholangiocarcinomas. Reports of right hepatectomy for patients with these lesions show higher frequencies of tumor-free margins and longer survival time [16,17,18], but at the cost of increased morbidity and mortality [6,7]. Chen et al [19] conducted a retrospective review of 138 cases of cholangiocarcinoma resection and concluded that minor liver resection of Bismuth type I and II cholangiocarcinoma, selected by predetermined criteria, achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the standard therapy for HC is major hepatectomy combined with extrahepatic biliary tree resection and lymphadenectomy. 9,90–92 Left hepatectomy is required for Bismuth-Corlette IIIb lesions, while Bismuth-Corlette I, II, and IIIa lesions will usually require an extended right hepatectomy. In addition, simultaneous caudate lobe resection is highly recommended given its association with improved long-term survival and decreased local recurrence rates.…”
Section: Surgical Managementmentioning
confidence: 99%